Indian telegraph act, 1885 ( act no. 13 of 1885) - Professional Book Publication (Delhi: Professional Book Publication, 2023)
Indian Telegraph Act, 1885 alongwith Indian Telegraph Rules, 1951
Keywords: Indian Telegraph Rules, 1951; Bare Act